New Pantene Indonesia Miracles Hair Supplement Viral Marketing Network and Comments on the Pantene Indonesia Youtube Account - Nuryanto, Guyub; Sariyati, Sariyati; Makmun, Makmun; G, Layla Dominique (Lentera Ilmu Nusantara, 2024)
Viral marketing is the main goal of marketers in conveying messages so that their products or services can be seen by many people. However, viral marketing does not always receive a positive response from the public. In this research, researchers want to see how a network is formed so that the new Pantene Miracles Hair Supplement advertisement can go viral and comments related to the advertisement on YouTube. This research uses the social network analytic method by analyzing networks and YouTube comments with the help of the Netlytic application. The results found that the network on YouTube did not form large groups because many comments stood alone, while the comments tended to be positive.